1976
DOI: 10.1016/s0022-5347(17)58727-3
|View full text |Cite
|
Sign up to set email alerts
|

Adult Ureteral Ectopia

Abstract: We report on 6 women with ureteral ectopia to emphasize the need for careful endoscopic examination in evaluating the entity. The clinical histories are unusual in that 1 of the 6 patients had classical symptoms of urinary incontinence. A discussion of the diagnosis and treatment of ureteral ectopia in such patients is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The ureter draining the lower moiety, although normally located, has a shorter intramural course at the vesicoureteric junction and is more prone to reflux and infection (Bissett and Strife, 1987;Sutton, 1987). When complete duplication is present it is the ureter draining the upper moiety that is ectopic (Persky and Noseworthy, 1976;Young and Lebowitz, 1987); the pelvicaliceal system associated with it is frequently abnormal (Yue, 1974). Ureteroceles may be present and are often associated with a dysplastic or obstructed upper moiety, or both (Young and Lebowitz, 1986;Sutton, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ureter draining the lower moiety, although normally located, has a shorter intramural course at the vesicoureteric junction and is more prone to reflux and infection (Bissett and Strife, 1987;Sutton, 1987). When complete duplication is present it is the ureter draining the upper moiety that is ectopic (Persky and Noseworthy, 1976;Young and Lebowitz, 1987); the pelvicaliceal system associated with it is frequently abnormal (Yue, 1974). Ureteroceles may be present and are often associated with a dysplastic or obstructed upper moiety, or both (Young and Lebowitz, 1986;Sutton, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…This may be difficult to demonstrate, although it is suggested that it may occur in approximately onethird of cases (Wyly and Lebowitz, 1984). The ectopic ureter may insert anywhere along the genitourinary tract (Sutton, 1987), classically giving rise to symptoms of wetness or dribbling since childhood (Persky and Noseworthy, 1976;Young and Lebowitz, 1986). Incontinence is not always present, however, and patients may present with other genitourinary symptoms, for example vaginal discharge (Persky and Noseworthy, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations